Algumas notas sobre as invasões francesas em Portugal na historiografia do século XIX - Marques, João Francisco (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The French invasions are a key moment in the late Portuguese Ancien Régime and rise of the Liberal movement. Therefore, the importance of reviewing and conducting comparative studies by historians such as Henrique Schaeffer, Oliveira Martins and Pinheiro Chagas, whose works greatly contributed to the 19th-century Portuguese historiography in spite of its ideological veil.